Estimation of nonparametric conditional moment models with possibly nonsmooth moments - Xiaohong Chen; Demian Pouzo (Centre for Microdata Methods and Practice (cemmap), 2008)
This paper studies nonparametric estimation of conditional moment models in which the residual functions could be nonsmooth with respect to the unknown functions of endogenous variables. It is a problem of nonparametric nonlinear instrumental variables (IV) estimation, and a difficult nonlinear ill-posed inverse problem with an unknown operator. We first propose a penalized sieve minimum distance (SMD) estimator of the unknown functions that are identified via the conditional moment models. We then establish its consistency and convergence rate (in strong metric), allowing for possibly non-compact function parameter spaces, possibly non-compact finite or infinite dimensional sieves with flexible lower semicompact or convex penalty, or finite dimensional linear sieves without penalty. Under relatively low-level sufficient conditions, and for both mildly and severely ill-posed problems, we show that the convergence rates for the nonlinear ill-posed inverse problems coincide with the known minimax optimal rates for the nonparametric mean IV regression. We illustrate the theory by two important applications: root-n asymptotic normality of the plug-in penalized SMD estimator of a weighted average derivative of a nonparametric nonlinear IV regression, and the convergence rate of a nonparametric additive quantile IV regression. We also present a simulation study and an empirical estimation of a system of nonparametric quantile IV Engel curves.
Keywords: C13; C14; D12; 330; nonsmooth residuals; nonlinear ill-posed inverse; penalized sieve minimum distance; modulus of continuity; average derivative of a nonparametric nonlinear IV regression; nonparametric additive quantile IV regression; Schätztheorie; Nichtparametrisches Verfahren; Regression; Momentenmethode